2021
DOI: 10.1038/s41438-021-00617-9
|View full text |Cite
|
Sign up to set email alerts
|

Genome-level diversification of eight ancient tea populations in the Guizhou and Yunnan regions identifies candidate genes for core agronomic traits

Abstract: The ancient tea plant, as a precious natural resource and source of tea plant genetic diversity, is of great value for studying the evolutionary mechanism, diversification, and domestication of plants. The overall genetic diversity among ancient tea plants and the genetic changes that occurred during natural selection remain poorly understood. Here, we report the genome resequencing of eight different groups consisting of 120 ancient tea plants: six groups from Guizhou Province and two groups from Yunnan Provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 54 publications
0
32
0
Order By: Relevance
“…These findings suggest that E. onukii spatially expanded to its currently distributed regions in the post‐LGM era, similar to many species in temperate North America and Europe 1,87 . Archaeological records showed that the western parts of China might be the region in which tea was first cultivated outside the native location of tea trees, dated to 2000 years ago (the Western Han Dynasty) 16,81–83,88 . Tea was disseminated to the north and east of its native region approximately 1000 years ago (from the Three Kingdoms to the Tang Dynasty) 88 .…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that E. onukii spatially expanded to its currently distributed regions in the post‐LGM era, similar to many species in temperate North America and Europe 1,87 . Archaeological records showed that the western parts of China might be the region in which tea was first cultivated outside the native location of tea trees, dated to 2000 years ago (the Western Han Dynasty) 16,81–83,88 . Tea was disseminated to the north and east of its native region approximately 1000 years ago (from the Three Kingdoms to the Tang Dynasty) 88 .…”
Section: Discussionmentioning
confidence: 99%
“…Tea is consumed by over three billion people across 160 countries, making it one of the world’s most popular beverages [ 9 , 10 ]. Its management as a cash crop plays an important role in rural poverty reduction [ 2 , 11 ] and economic growth.…”
Section: Introductionmentioning
confidence: 99%
“…Some trees in tea gardens regrow from the original ancient trunks. According to Lu et al [ 9 ], there is no official definition of ancient tea trees, but natural trees over 100 years of age are often considered ancient. Hence, we define wild trees over 100 years or trees regrown from trunks over 100 years of age as ancient in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Tea from ancient trees fetches high prices because of its rarity and flavor. "Ancient" trees are often defined as trees over 100 years of age or regrown trees from trunks over 100 years of age [10]. Tea from ancient trees has unique properties.…”
Section: Introductionmentioning
confidence: 99%
“…According to Zhao et al [11], ancient tea is rich in nutrients, and the genetic diversity of these ancient trees significantly contributes to tea cultivation. Lu et al [10] indicated that the study of the genes of ancient trees under natural selection can provide insights into the evolutionary mechanisms, diversification, and domestication of trees and aid the functional characterization and genetic improvement of trees. A photochemical analysis of ancient Pu'er tea trees suggests that their high polyphenol concentration has detoxifying and elastin-protecting properties, which slows skin aging [12].…”
Section: Introductionmentioning
confidence: 99%